Unveiling Integrated Functional Pathways Leading to Enhanced Respiratory Disease Associated With Inactivated Respiratory Syncytial Viral Vaccine - Russell, Marsha S.; Creskey, Marybeth; Muralidharan, Abenaya; Li, Changgui; Gao, Jun; Chen, Wangxue; Larocque, Louise; Lavoie, Jessie R.; Farnsworth, Aaron; Rosu-Myles, Michael; Hashem, Anwar M.; Yauk, Carole L.; et al. (Frontiers in Immunology, 2019)
Respiratory syncytial virus (RSV) infection is a severe threat to young children and the elderly. Despite decades of research, no vaccine has been approved. Notably, instead of affording protection, a formalin-inactivated RSV vaccine induced severe respiratory disease including deaths in vaccinated children in a 1960s clinical trial; however, recent studies indicate that other forms of experimental vaccines can also induce pulmonary pathology in pre-clinical studies. These findings suggest that multiple factors/pathways could be involved in the development of enhanced respiratory diseases. Clearly, a better understanding of the mechanisms underlying such adverse reactions is critically important for the development of safe and efficacious vaccines against RSV infection, given the exponential growth of RSV vaccine clinical trials in recent years. By employing an integrated systems biology approach in a pre-clinical cotton rat model, we unravelled a complex network of pulmonary canonical pathways leading to disease development in vaccinated animals upon subsequent RSV infections. Cytokines including IL-1, IL-6 GRO/IL-8 and IL-17 in conjunction with mobilized pulmonary inflammatory cells could play important roles in disease development, which involved a wide range of host responses including exacerbated pulmonary inflammation, oxidative stress, hyperreactivity and homeostatic imbalance between coagulation and fibrinolysis. Moreover, the observed elevated levels of MyD88 implicate the involvement of this critical signal transduction module as the central node of the inflammatory pathways leading to exacerbated pulmonary pathology. Finally, the immunopathological consequences of inactivated vaccine immunization and subsequent RSV exposure were further substantiated by histological analyses of these key proteins along with inflammatory cytokines, while hypercoagulation was supported by increased pulmonary fibrinogen/fibrin accompanied by reduced levels of plasma D-dimers. Enhanced respiratory disease associated with inactivated RSV vaccine involves a complex network of host responses, resulting in significant pulmonary lesions and clinical manifestations such as tachypnea and airway obstruction. The mechanistic insight into the convergence of different signal pathways and identification of biomarkers could help facilitate the development of safe and effective RSV vaccine and formulation of new targeted interventions.